Vanadium Diselenide Single Crystals: Van der Waals Epitaxial Growth of 2D Metallic Vanadium Diselenide Single Crystals and their Extra‐High Electrical Conductivity (Adv. Mater. 37/2017). Issue 37 (4th October 2017) - Zhang, Zhepeng; Niu, Jingjing; Yang, Pengfei; Gong, Yue; Ji, Qingqing; Shi, Jianping; Fang, Qiyi; Jiang, Shaolong; Li, He; Zhou, Xiebo; Gu, Lin; Wu, Xiaosong; et al.
Abstract : In article number 1702359, Yanfeng Zhang and co‐workers report a van der Waals epitaxy route for the chemical vapor deposition growth of few‐layer metallic 1T‐phase VSe2 crystals on mica substrates, and uncover its extra‐high electrical conductivity and thickness‐dependent charge‐density wave transitions. This work sheds light on the synthesis and property investigations of nanoscale‐thickness 2D metallic transition‐metal dichalcogenide crystals.